High microwave responsivity Co–Bi25FeO40 in synergistic activation of peroxydisulfate for high efficiency pollutants degradation and disinfection: Mechanism of enhanced electron transfer. (February 2022) - Li, Shuo; Wu, Yanan; Zheng, Heshan; Zheng, Yongjie; Jing, Tao; Tian, Jingzhi; Ma, Jun; Na, Jun
Abstract: Cobalt doped Bi25 FeO40 was used as a heterogeneous catalyst in microwave (MW) co-activation of peroxydisulfate (PDS) system for organic contaminant purification and disinfection simultaneously. Due to low charge-transfer resistance and fast electron migration, Co–Bi25 FeO40 showed superior catalytic efficiencies for activation PDS to degrade over 92.0% of bisphenol A (BPA) with the initial concentrations ranging from 40 mg/L to 120 mg/L in 5.0 min. The non-radical oxidation pathway via electron transfer regime on the surface of Co–Bi25 FeO40 was the dominant reactive species in the reaction system. Benefit from the energy transfer and cross-coupling reactions of microwave, the Co–Bi25 FeO40 /MW/PDS system can generate abundant reactive sites to facilitate the formation of more surface-bonding complexes. Microwave energy can be absorbed by Co–Bi25 FeO40 catalysts to promote activation of PDS and production of nanobubbles. The generated nanobubbles increase the temperature of the local solution to promote the reaction. The Co–Bi25 FeO40 /MW/PDS system also exhibited excellent bactericidal capability for Escherichia coli (E.coli) . The catalysts, oxidants and microwaves acted on E. coli to form physical, and oxidative pressure simultaneously, causing cell damaged and made bacterial death. This work provides prospects toward high-efficiency integration of contaminant purification and pathogenic microorganisms inactivation. Graphical abstract: Image 1 Highlights: Co–Bi25 FeO40 material with high microwave responsiveness has high efficiency on BPA degradation. Cobalt doping enhanced the Bi25 FeO40 intrinsic property and electron transfer for BPA degradation. Co–Bi25 FeO40 /MW/PDS system exhibited excellent disinfection efficiency towards E. coli.